2012
DOI: 10.1097/md.0b013e318243442b
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-Resistant Staphylococcus aureus Meningitis in Adults

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) meningitis is an uncommon disease, and little is known about its epidemiology, clinical features, therapy, and outcome. We performed a multicenter retrospective study of MRSA meningitis in adults. Eighty-six adult patients were included and the following data were obtained: underlying diseases, clinical presentation, analytical and microbiologic data, response to therapy, and outcome.There were 56 men (65%) and the mean age was 51.5 years; 54 of them (63%) had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…The mortality rate for hematogenous S. aureus meningitis is higher (43 to 50%) than that occurring postsurgically (14 to 25%) (780,787). Among S. aureus meningitis cases, methicillin resistance has been increasing in recent years (786,(789)(790)(791). Specifically, Pintado et al conducted a retrospective, multicenter study examining MRSA meningitis in adults over a 25-year period (1981 to 2005).…”
Section: Meningitismentioning
confidence: 99%
See 3 more Smart Citations
“…The mortality rate for hematogenous S. aureus meningitis is higher (43 to 50%) than that occurring postsurgically (14 to 25%) (780,787). Among S. aureus meningitis cases, methicillin resistance has been increasing in recent years (786,(789)(790)(791). Specifically, Pintado et al conducted a retrospective, multicenter study examining MRSA meningitis in adults over a 25-year period (1981 to 2005).…”
Section: Meningitismentioning
confidence: 99%
“…The 30-day mortality rate for these patients was 31%. Most MRSA meningitis cases are nosocomial and postsurgical (786,789).…”
Section: Meningitismentioning
confidence: 99%
See 2 more Smart Citations
“…Meningitis, caused by hematogenous spread, or acquired post-neurosurgery is of rising incidence and importance especially due to an increase in methicillin-resistant S. aureus (MRSA) strains in recent years. Although MRSA-mediated meningitis is rare, it has a high mortality rate, and is therefore a very serious disease (Aguilar et al, 2010; Pintado et al, 2012). Studies on the effect of S. aureus LTA on rat brain cells have shown that it can induce cerebellar neuronal cell death but only in the presence of glial cells.…”
Section: Other Bacteriamentioning
confidence: 99%